SPE Annual Technical Conference and Exhibition 1994
DOI: 10.2118/28505-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Light Ends and High Pressure on Paraffin Formation

Abstract: A thermodynamic model for paraffin formation is presented which accurately accounts for the effects of light ends, such as methane, ethane, and propane, and high pressures. The model uses the Simplified, Perturbed Hard Chain equation of state for all fluid phase fugacities and contains no adjustable parameters for the solid-liquid equilibria. Model predictions are compared to binary solid-liquid, solid-vapor, and solid-liquid-vapor equilibria data with good results. Also, a high-pressure, coldstage microscope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…STO WAT gives higher value than live oil WAT of the same crude oil. This is to be expected, as light ends increase the solubility of paraffin molecules (Huanquan et al, 1997), while increase in pressure depresses the WAT below the bubblepoint pressure (Brown et al, 1994). The entire wax deposition process is complex.…”
Section: Wat and Wdt Results And Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…STO WAT gives higher value than live oil WAT of the same crude oil. This is to be expected, as light ends increase the solubility of paraffin molecules (Huanquan et al, 1997), while increase in pressure depresses the WAT below the bubblepoint pressure (Brown et al, 1994). The entire wax deposition process is complex.…”
Section: Wat and Wdt Results And Discussionmentioning
confidence: 95%
“…Here wax appearance temperature decreases with increase in pressure up to bubblepoint pressure (Brown et al, 1994) due to dissolution of light ends back into the liquid phase. The WAT increases with increase in pressure for STO, commonly referred to as dead oil (Brown et al, 1994;Karan et al, 2000). Huanquan et al (1997) reported that the WAT increases with increase in pressure for a fixed component liquid mixture.…”
Section: Pressurementioning
confidence: 98%
See 1 more Smart Citation
“…There has been a great deal of work on the thermodynamic models for predicting paraffin (or wax) precipitakion from oils (Weingarten and Euchner, 1988;Won, 1985,19SG,19S9;Hansen, 1988;Pedersen, 1991;Brown, 1994). Ring and Wattenbarger (1992) developed a computer simulator for predicting oil recovery in paraffinic crude reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations illustrate that reasonable predictions could be obtained by using the simplest of the Won's models (neglecting the effect of activity coefficients) with heats of fusion modification proposed by Pedersen et a1 (Pedersen, Skovborg and Ronningsen, 1991). Won's most recent model (1989) and some of the more recent models (Brown, et al, 1994) were not compared in this study.…”
mentioning
confidence: 99%